Pemodelan Ekspor Turunan CPO Indonesia ke China Periode 2007-2023 dengan ARDL - Clarissa Azarine; Timbang Sirait; Nurvita Trianasari (Limits: Journal of Mathematics and Its Applications, 2026)
Exports play a vital role in supporting Indonesia’s economic growth, with crude palm oil (CPO) derivative products being among its top export commodities. China serves as a primary export destination, however, since 2019, shipments to the country have exhibited a declining trend. This study aims to analize the long-term and short-term determinants of Indonesian CPO derivative exports to China using the Autoregressive Distributed Lag (ARDL) model. This study uses secondary data sourced from Statistics Indonesia (BPS), National Bureau of Statistics of China (NBS China), International Monetary Fund (IMF), and Ministry of Finance of the Republic of Indonesia. The results of this study show that, in the long-term, the CPO production positively influences exports, whereas export prices have a negative effect. While in the short-term, exports and China's Gross Domestic Product (GDP) in the current and previous periods, as well as export duties, have a positive effect, whereas previous CPO production has a negative effect. These results highlight the significant roles of both domestic and external factors in shaping export performance, underscoring the need for strategies that address price fluctuations, ensure production stability, and consider the economic conditions and policies of trading partners